Efecto terapéutico de la ozonoterapia en la cicatrización de heridas en perros - Manzo Aldaz, Valeria Dayanna (2022)
For the elaboration of the present thesis a research work was conducted about the therapeutical effect of ozone therapy in the healing of wounds in dogs. The process of ozone application in the medicinal area is known as ozone therapy, and can be used in veterinary medicine as in human medicine. Among the benefits of ozone therapy, there is its contribution to the augmentation of availability of oxygen and Adenosine triphosphate (ATP) for the cellular activity, the inactivation of harmful microorganisms, its anti-inflammatory effect, regenerative properties, analgesic properties and its treatment in cutaneous and muscular wounds. It is this last property the most pertinent to the development of this research because ozone has emollient, healing, anti-bacterial, and disinfectant properties. The research is based on scientific articles in journals of veterinary medicine, in Spanish and English. However, although the uses of ozone as a medicinal treatment are several, the studies published about the use of ozone in small animals are limited, some results being originated of empirical and experimental exercises with tests subjected to revision and analysis regarding the clinical effects obtained. Most of the results are presented as positive conclusions, but at the same time uncertain leading to controversy about the present and future use of ozone therapy and further studies are recommended. Literature mentions clinical improvement after the use of ozone therapy and it is suggested as an alternative treatment or complementary to treat certain pathologies.